2016
DOI: 10.1002/wsb.640
|View full text |Cite
|
Sign up to set email alerts
|

What are snow leopards really eating? Identifying bias in food-habit studies

Abstract: Declining prey populations are widely recognized as a primary threat to snow leopard (Panthera uncia) populations throughout their range. Effective snow leopard conservation will depend upon reliable knowledge of food habits. Unfortunately, past food-habit studies may be biased by inclusion of nontarget species in fecal analysis, potentially misinforming managers about snow leopard prey requirements. Differentiation between snow leopard and sympatric carnivore scat is now cost-effective and reliable using gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…All these results are very different from ours. However, these studies most likely overestimated the importance of small prey [66], because none of them used genetic methods for identifying the depositor of the scat and studies solely based on visual identification of samples may be strongly biased. Actually, our molecular analyses revealed that as much as 50% of the scats collected, which looked like snow leopard scats, in fact belonged to other carnivores, which is a number similar to that reported in other studies [21, 23, 26, 39, 67].…”
Section: Discussionmentioning
confidence: 99%
“…All these results are very different from ours. However, these studies most likely overestimated the importance of small prey [66], because none of them used genetic methods for identifying the depositor of the scat and studies solely based on visual identification of samples may be strongly biased. Actually, our molecular analyses revealed that as much as 50% of the scats collected, which looked like snow leopard scats, in fact belonged to other carnivores, which is a number similar to that reported in other studies [21, 23, 26, 39, 67].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this seasonal signature in diet variability is present throughout the terrestrial ecosystems, where a continuous adjustment of diet to seasonal fluctuation of resource availability is observed (from lizards to larger mammals; e.g., Bergmann et al, ; Kartzinel & Pringle, ). DNA metabarcoding has also been able to clarify the feeding ecology of terrestrial elusive species, for example, in the case of the snow leopard Panthera uncia (Shehzad, McCarthy, et al, ; Weiskopf, Kachel, & McCarthy, ) and that of large African mammalian herbivores, for which the diet composition was found to strongly differ across newly identified cryptic species, irrespective of feeding guild (Kartzinel et al, ). Ultimately, there was also an increased value of metabarcoding approaches to study the feeding ecology of endangered species, where the accurate description of dietary habits is crucial to the design and enforcement of conservation and management strategies.…”
Section: Confirmation Of Terrestrial Dietary Preferences and A Paradimentioning
confidence: 99%
“…Misidentification in predator's identity from scat, due to the presence of co-predators, can introduce bias in estimating diets (Weiskopf et al 2016). We relied on several facts and precautions as lines of evidence in order to reduce or eliminate any potential bias.…”
Section: Predator Identitymentioning
confidence: 99%